2015
DOI: 10.1371/journal.ppat.1004925
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus on Oceanic Islands: Host and Viral Diversity in Seabirds in the Western Indian Ocean

Abstract: Ducks and seabirds are natural hosts for influenza A viruses (IAV). On oceanic islands, the ecology of IAV could be affected by the relative diversity, abundance and density of seabirds and ducks. Seabirds are the most abundant and widespread avifauna in the Western Indian Ocean and, in this region, oceanic islands represent major breeding sites for a large diversity of potential IAV host species. Based on serological assays, we assessed the host range of IAV and the virus subtype diversity in terns of the isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…An ELISA targeting the nucleoprotein, an antigen known to be shared by all the subtypes of the virus, is generally used to first screen efficiently all the samples. In a second step, the ELISA positive samples can be analysed using inhibition of haemagglutination assays specific to each viral subtype (Lebarbenchon et al., ) or increasingly available multiplex assays (Freidl et al., ). Another example deals with the circulation of flaviviruses in bird populations: ELISA screening using an assay specific for a broad range of flaviviruses has been efficiently implemented to detect populations with positive samples that have then been analysed using more specific virus neutralization assays (Arnal et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…An ELISA targeting the nucleoprotein, an antigen known to be shared by all the subtypes of the virus, is generally used to first screen efficiently all the samples. In a second step, the ELISA positive samples can be analysed using inhibition of haemagglutination assays specific to each viral subtype (Lebarbenchon et al., ) or increasingly available multiplex assays (Freidl et al., ). Another example deals with the circulation of flaviviruses in bird populations: ELISA screening using an assay specific for a broad range of flaviviruses has been efficiently implemented to detect populations with positive samples that have then been analysed using more specific virus neutralization assays (Arnal et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…molecular biology, virus isolation) in sometimes high security laboratories such as for highly pathogenic avian influenza and West Nile viruses is needed, and certain biological safety precautions are required by law in some regions (e.g. Allison et al, 2015;Lebarbenchon et al, 2010Lebarbenchon et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the idea that bird age is an important factor involved in influenza virus infection. Investigations of virus transmission on tropical oceanic islands have also shown that terns could be involved in the introduction and maintenance of avian influenza viruses in these remote locations (Lebarbenchon et al, 2015).…”
Section: Avian Influenzamentioning
confidence: 99%
“…These islands are uninhabited or host small human communities (these islands are mainly nature reserves, military camps, or privately owned), except for Réunion island (800 000 inhabitants). The same sampling strategy was performed as in a previous investigation on influenza A virus infection in seabirds performed on the same bird communities and islands [32]. The most abundant and diverse bird species were sampled on each island by taking into account geographical, safety, ethical and sample conservation constraints.…”
Section: Methodsmentioning
confidence: 99%